SYSTEMATIC REVIEW: ANAPLASTIC LARGE CELL LYMPHOMA FOLLOWING BREAST IMPLANT SURGERY - Eveline, Kezia; Lestari, Rizqi Shabrina; Beta Subakti Nata’admadja; Adzalika, Lavonia Berlina (Universitas Airlangga, 2023)
Highlights: BIA-ALCL, a T-cell lymphoma associated with breast implants, is posing a growing medical challenge due to the increasing use of implants for cosmetic and reconstructive purposes The majority of BIA-ALCL cases were associated with cosmetic reasons for breast implants, and textured implants were predominantly implicated. Abstract: Introduction: BIA-ALCL, a T-cell lymphoma associated with breast implants, poses a growing medical challenge despite its relatively low occurrence, due to the increasing use of implants for cosmetic and reconstructive purposes. Our objective is to review the incidence, characteristics of patients, implant types, management, and outcome of BIA-ALCL. Methods: Pubmed and Science Direct databases were searched to identify case series and observational research. A systematic review was conducted by looking up the keywords